AB0721 Usefullness of Intravenous Immunoglobulin in Treatment of Polimyositis Dermatomyositis. Report of a Single Center. (9th June 2015) - Faggioli, P.; Tamburello, A.; Sciascera, A.; Gilardi, A.G.; Rondena, M.; Giani, L.; Mazzone, A.
Abstract : Background: Many studies and review have been published concerning the use of hight does of immunoglobulin (IVG) in treatment of polymiositis (PM) or dermatomyositis (DM). Usually this treatment is not employed as first-line therapy, but in relapsing or in no response to conventional immunomodulator therapies. Normally the standard doses of IVG is 2 g/kg in 5 days, very rarely in 2 days and the treatment is usually continued for 3-6 months. Adverse effects are generally few and generally tolerable. Objectives: We report our case series in which IVG were used a first therapeutic choice in order to induce a faster remission in acute PM-DM presentation. Methods: We observed 15 patients (pts) (4M/11F) mean age 42, 6 y (28-72 y) affected by acute PM – DM. Nobody developed a paraneoplastic syndrome. At the onset the mean values of serum creatin kinase (CPK) were 2980 U/l (nv<200 u/L) (range CPK 2430-9100 U/l) and mean values of myoglobin (MG) were 420 ng/ml (nv<120 ng/ml). Antinucelar antibodies (ANA) specked pattern, were positive in all patients at medium tiltle, 3 pts (2 F/1M) showed positivity for myositis antibodies, nobody were Jo1 positive and 1 pt showed later a positivity for U1NRP. All pts showed a legs weakness, 2 pts dyspnea in moderate exercise, 1 pt showed generalized weakness with difficulty to maintain the posture of the head and bilateral mydriasis, 2 patients reported dysphagia for solid and liquid foods, 5 pts showed a reticular pattern at pulmonary high resolution TC (HRTC) All patients after an initial treatment with corticosteroids (3 pts received also high dose 6-metilprednisolon 1gr/day for 3 days) were treated her with immunoglobulin at a dose of 2g/kg distributed in 5 days for 6 months. Results: After 3 infusions the CPK and MG levels were reduced to 70% compared to baseline and normalized after 5 infusions. The mean dosage of corticosteroid was gradually reduced and some immunosuppressant agents (Cyclosporin A in 2 pts, Mycophenolate Mofetile in 2 pts, Azathioprine in 3 pts), were gradually introduced while the other patients continued with a minimum dose of prednisone (5 mg/day), maintaining a complete remission. Dysphagia, short breath, mydriasis were completely resolved, a mild legs weakness persisted until the 6ht month, at HRCT also reticular pattern were improved. Conclusions: The treatment with IVG in severe or rapidly progressive PM-DM has been documented in many open-label trials to be effective, especially in pts with lung involvement and esophageal involvement. Adverse effects were generally tolerable and therefore, it may propose the use of IGV use is suggested to induce a faster remission and to allow a faster tapering of the corticosteroid and introduction of immunosuppressive drugs. References: Wan DX et al. Rheumatology 2012;31:801-6. Danieli MG et al. Autoimmun Rev 2014;13:1048-54. Disclosure of Interest: None declared